Angel's peak ebook - Carr, Robyn (Virgin River, 2012)
Welcome back to Virgin River with the books that started it all... Four years ago, air force sweethearts Franci Duncan and Sean Riordan reached an impasse. She wanted marriage and a family. He didn't. But a chance meeting proves that the bitter breakup hasn't cooled their sizzling chemistry. Sean has settled down in spite of himself—he's not the cocky young fighter pilot he was when Franci left, and he wants them to try again. After all, they have a history...but that's not all they share. Franci's secret reason for walking away when Sean refused to commit is now three and a half: a redheaded cherub named Rosie who shares her daddy's emerald-green eyes. Sean is stunned—and furious with Franci for the deception. News travels fast in Virgin River, and soon the whole town is taking sides. Rebuilding their trust could take a small miracle—and the kind of love that can move mountains. What you can expect in Angel's Peak: Small Town Romance Secret Baby Second Chance Romance Ex-Military Hero + Heroine Don't miss Robyn Carr's next uplifting novel, The Friendship Club, where four women come together at a tumultuous time in their lives, forging an unbreakable bond that will leave them all forever changed! Virgin River Novels: Book 1: Virgin River Book 2: Shelter Mountain Book 3: Whispering Rock Book 4: A Virgin River Christmas Book 5: Second Chance Pass Book 6: Temptation Ridge Book 7: Paradise Valley Book 8: Forbidden Falls Book 9: Angel's Peak Book 10: Moonlight Road Book 11: Promise Canyon Book 12: Wild Man Creek Book 13: Harvest Moon Book 14: Bring Me Home for Christmas Book 15: Hidden Summit Book 16: Redwood Bend Book 17: Sunrise Point Book 18: My Kind of Christmas Book 19: Return to Virgin River